Hedging the Foreign Currency Risk in Nigeria (Eurasian Journal of Humanities and Social Sciences, 2025)
The management of currency risk exposure has become increasingly significant over the past decade due to the frequent emergence of numerous currency crises. The Nigerian national currency, the Naira, has experienced multiple exchange rate fluctuations over the past three decades. The currency's value has fluctuated significantly and rapidly multiple times, affecting both visible and invisible trade. It is prevalent today to observe numerous countries engaged in imports and exports, as well as consumers lamenting the detrimental effects of these trends, which are evident in the overall increase in prices of goods and services. Research indicates that numerous Nigerian foreign traders, especially within the small and medium sector, either lack fundamental knowledge regarding the management of foreign exchange risk or are doubtful about its effectiveness. From the perspective of corporate management, currency risk management is increasingly regarded as a productoriented strategy to mitigate a bank or firm's exposure to significant exchange rate fluctuations.